Information technologies in teaching a foreign language ("Conference on Universal Science Research 2023", 2023)
The following article deals with development of education, which organically linked with an increase in the level of its information potential. This characteristic feature largely determines both the direction of the evolution of education itself and the future of the whole society. For the most successful orientation in the global information space, it is necessary for students to master information culture, as well as computer-screen culture, since the Internet is increasingly given priority in the search for information. The creation of the Internet, or World Wide Web, has become one of the most revolutionary achievements of the last decades, affecting the educational process on a global scale.